More women on Indian boards: moving beyond mere regulations and tokenism. Issue 3 (14th March 2016) - Pathak, Atul Arun; Purkayastha, Anish
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by independent writers who add their own impartial comments and place the articles in context. Findings: – In patriarchal societies such as India, there is great reluctance to allow women to take up leadership roles. Although the benefits of gender diversity in board composition are understood by organizations, there is limited progress. The government, companies and women who are potential board members all need to coordinate and work together towards solving this issue in the long run. Research limitations/implications: – Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Social implications: – Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.